Students' attitudes towards starting a business, on the example of students at the University of Information Technology and Management in Rzeszów (Poland) - Karolina Palimąka; Jacek Rodzinka (e-Finanse: Financial Internet Quarterly, 2018)
Entrepreneurship understood as a manifestation of economic activity is an issue widely discussed in literature, especially in the field of economics. Today, a large part of society is involved in establishing and running a business, hence the shaping of entrepreneurial behaviors gains importance among all age groups, especially young people. The main objective of the conducted research was to examine the interest in starting their own business by students and to verify whether the direction of their studies or role in the group affects the students' willingness to start a business and whether a family member runs a business influences this interest and moreover, whether capital and the idea are the two main criteria conditioning the decision.. The conclusions were based on a study, i.e. (mainly) the cross-analysis of data collected as part of a survey conducted among students of the University of Information Technology and Management in Rzeszów.
Keywords: L26; A20; 330; entrepreneurship; starting a business; students